Analisis Pemanfaatan Website Inaportnet Dengan Menggunakan Pendekatan Fuzzy Service Quality - Adhelia Salsabila; Amelia Yusnita; Rizky Zakariyya Rasyad (Management of Information System Journal, 2026)
This study aims to analyze the effectiveness of the use of the Inaportnet website at PT BTJ Tanah Grogot to improve service quality and public trust. By using the Fuzzy Service Quality (Fuzzy SERVQUAL) approach, this study assesses the level of gap that occurs between user expectations and their perceptions in the field. through five dimensions of service quality. The results of data processing There are differences in each variable, which indicates that the discrepancy is negative, which indicates that the quality of service available has not reached the maximum point of meeting user expectations. The Reliabilitiy dimension is the main priority for improvement with the largest gap value of -0.85, while the Tangibles dimension has the best performance or is closest to user expectations with the smallest gap value of -0.20. Overall, managers are advised to make tactical improvements, especially in the aspect of system reliabilitiy for the smooth operation of maritime logistics.